The Efficiency of the TDABC Model in Calculating the Time-Driven Costs of Car Maintenance: An Applied Study in Renault Services Agency - Ain M'lila- - zeroual, abderrachid; berkem, zouhir (Journal of Research in Finance and Accounting, 2024)
This study aims to apply the Time-Driven Activity-Based Costing (TDABC) model to measure the costs of maintenance and repair services in the automotive sector. We adopted the descriptive-analytical approach and utilized the case study tool. The results showed that the TDABC model offers high flexibility and efficiency in its implementation, even with the diversity and complexity of maintenance services activities. This model provides the ability to accurately determine and measure the cost of maintenance services, in addition to calculating the total time required for each service. This enables management to make strategic decisions based on precise data, aimed at reducing costs and increasing profits.